GEOLOGICAL EVIDENCE FOR INTRA-JURASSIC FAULTING IN THE WESSEX BASIN AND ITS MARGINS - Jenkyns, H; Senior, J (1991)
Geological observations on Jurassic outcrops close to major faults in the Wessex Basin- Mendip area reveal the local presence of ammonite- and brachiopod-bearing sediments penetrating underlying strata. Toarcian and Bajocian neptunian dykes and particularly sills are associated with the Eypemouth Fault and Bajocian sills with the Bride Fault and Mere Fault. In the Mendip area numerous neptunian dykes of Hettangian, Sinemurian, Pliensbachian and Bajocian ages, cross-cutting Carboniferous Limestone, are recorded, typically also associated with major basement faults (e.g. Cranmore and Leighton Faults). These periods of assumed sediment injection are taken as indicating times of displacement along the faults in question. Variations in facies (Hettangian-Sinemurian, Toarcian, Bajocian, uppermost Oxfordian, Kimmeridgian) spatially linked to faults are documented from some areas, and boreholes reveal considerable fault-controlled thickness changes in Hettangian-Sinemurian, Bajocian and Kimmeridgian sediments. The timing of Jurassic faulting in the Wessex Basin-Mendip area thus polarizes into two intervals: Hettangian-Bajocian and latest Oxfordian onwards, correlating withth e early rifting phases of the Central and North Atlantic respectively.